Concussion information online: evaluation of information quality, content and readability of concussion-related websites. Issue 9 (18th April 2011) - Ahmed, Osman H; Sullivan, S John; Schneiders, Anthony G; McCrory, Paul R
Abstract : Background: The internet plays an important role in the dissemination of health information to the general public. Information on orthopaedic sports medicine websites has been shown to be of a varying standard, and to date there has been no evaluation of the overall quality of concussion-related websites. Methods: A four-stage methodological sampling technique was used to identify concussion-related websites. Websites were assessed for the presence of a quality standard (the HONcode ), their adherence to current expert concussion knowledge using a custom-developed concussion checklist ('CONcheck'), and their readability using the established Flesch Reading Ease (FRE) and Flesch–Kincaid Grade Level (FKGL). Results: 43 Websites were identified from the search strategy with the majority (70%) not HONcode certified. A wide distribution of scores was seen for the CONcheck (0–22), FRE (16.3–77.4) and FKGL (6–17.8). Statistical analysis using independent t tests between websites with the HONcode and websites without the HONcode showed no significant differences between the two groups for CONcheck (t41 =0.571, p=0.571), FRE (t41 =0.808, p=0.424) and FKGL(t41 =−0.964, p=0.341) scores. Conclusions: The variability in the standard of concussion-related websites highlights the need for sports medicine website providers to consider the delivery, content and readability of information to the public.